Language biographies and language repertoires : changes in language identity of indigenous African language speakers in a town in the Northern Cape - Daubney, Anna-Marie (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.